Eksistensi Bank Tanah Sebagai Lembaga Pengelolaan Tanah Negara - Bening Tyas Wijayanti; Arief Rahman; Wiwiek Wahyuningsih (Private Law, 2023)
This study aims to determine and analyze the existence of a land bank as a state land management agency and to find out how the land bank is regulated according to positive law in Indonesia. The method used is normative, and then the data is analyzed by descriptive analysis. The results of this study indicate that the land bank regulation according to positive law in Indonesia is in Government Regulation Number 64 of 2021 concerning the Land Bank Agency and the existence of the land bank as a state land management institution is that the land bank has the task of managing state land to become more valuable and beneficial following its designation. It is hoped that this land bank can become a helpful institution and run following favourable laws in Indonesia.